Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Spectroscopic detection of bioaerosols with the wibs-4+: Anthropogenic and meteorological impacts - Emma Markey; Jerry Hourihane Clancy; Moisés Martínez-Bracero; Roland Sarda-Estève; Dominique Baisnée; Eoin J. McGillicuddy; Gavin Sewell; Carsten Ambelas Skjøth; David J. O'Connor (Science of The Total Environment, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

A comprehensive aerobiological study of the airborne pollen in the Irish environment - Emma Markey; Jerry Hourihane Clancy; Moisés Martínez-Bracero; Jose María Maya-Manzano; Matt Smith; Carsten Skjøth; Paul Dowding; Roland Sarda-Estève; Dominique Baisnée; Aoife Donnelly; Eoin McGillicuddy; Gavin Sewell; et al. (Aerobiologia, 2022)
Respiratory allergies triggered by pollen allergens represent a significant health concern to the Irish public. Up to now, Ireland has largely refrained from participating in long-term aerobiological studies. Recently, pollen monitoring has commenced in several sampling locations around Ireland. The first results of the pollen monitoring campaigns for Dublin (urban) and Carlow (rural) concerning the period 2017–2019 and 2018–2019, respectively, are presented herein. Additional unpublished pollen data from 1978–1980 and, 2010–2011 were also incorporated in creating the first pollen calendar for Dublin. During the monitoring period over 60 pollen types were identified with an average Annual Pollen Integral (APIn) of 32,217 Pollen × day/m 3 for Dublin and 78,411 Pollen × day/m 3 for Carlow. The most prevalent pollen types in Dublin were: Poaceae (32%), Urticaceae (29%), Cupressaceae/Taxaceae (11%), Betula (10%), Quercus (4%), Pinus (3%), Fraxinus (2%), Alnus (2%) and Platanus (1%). The predominant pollen types in Carlow were identified as Poaceae (70%), Urticaceae (12%) , Betula (10%), Quercus (2%), Fraxinus (1%) and Pinus (1%). These prevalent pollen types increased in annual pollen concentration in both locations from 2018 to 2019 except for Fraxinus. Although higher pollen concentrations were observed for the Carlow (rural) site a greater variety of pollen types were identified for the Dublin (urban) site. The general annual trend in the pollen season began with the release of tree pollen in early spring, followed by the release of grass and herbaceous pollen which dominated the summer months with the annual pollen season coming to an end in October. This behaviour was illustrated for 21 different pollen types in the Dublin pollen calendar. The correlation between ambient pollen concentration and meteorological parameters was also examined and differed greatly depending on the location and study year. A striking feature was a substantial fraction of the recorded pollen sampled in Dublin did not correlate with the prevailing wind directions. However, using non-parametric wind regression, specific source regions could be determined such as Alnus originating from the Southeast, Betula originating from the East and Poaceae originating from the Southwest.

The COVID-19 pandemic: local to global implications as perceived by urban ecologists - Ian Douglas; Mark Champion; Joy Clancy; David Haley; Marcelo Lopes de Souza; Kerry Morrison; Alan Scott; Richard Scott; Miriam Stark; Joanne Tippett; Piotr Tryjanowski; Tim Webb (Socio-Ecological Practice Research, 2020)
The global COVID-19 pandemic is affecting everyone, but in many different ways, stimulating contrasting reactions and responses: opportunities for some, difficulties for many. A simple survey of how individual workers in urban ecology have been coping with COVID-19 constraints found divergent responses to COVID-19 on people’s activities, both within countries and between continents. Many academics felt frustrated at being unable to do fieldwork, but several saw opportunities to change ways of working and review their engagement with the natural world. Some engaging with social groups found new ways of sharing ideas and developing aspirations without face-to-face contact. Practitioners creating and managing urban greenspaces had to devise ways to work and travel while maintaining social distancing. Many feared severe funding impacts from changed local government priorities. Around the world, the COVID-19 pandemic has amplified issues, such as environmental injustice, disaster preparation and food security, that have been endemic in most countries across the global south in modern times. However, developing and sustaining the strong community spirit shown in many places will speed economic recovery and make cities more resilient against future geophysical and people-made disasters. Significantly, top-down responses and one-size-fits-all solutions, however good the modelling on which they are based, are unlikely to succeed without the insights that local knowledge and community understanding can bring. We all will have to look at disaster preparation in a more comprehensive, caring and consistent way in future.

Combined Feedforward/Feedback Control of an Integrated Continuous Granulation Process - Glinka Cathy Pereira; Shashank Venkat Muddu; Andrés David Román-Ospino; Don Clancy; Benoit Igne; Christian Airiau; Fernando J. Muzzio; Marianthi Ierapetritou; Rohit Ramachandran; Ravendra Singh (Journal of Pharmaceutical Innovation, 2019)

Multi-scale Modeling of the Cardiovascular System: Disease Development, Progression, and Clinical Intervention - Yanhang Zhang; Victor H. Barocas; Scott A. Berceli; Colleen E. Clancy; David M. Eckmann; Marc Garbey; Ghassan S. Kassab; Donna R. Lochner; Andrew D. McCulloch; Roger Tran-Son-Tay; Natalia A. Trayanova (Annals of Biomedical Engineering, 2016)

Multiscale Modeling in the Clinic: Drug Design and Development - Colleen E. Clancy; Gary An; William R. Cannon; Yaling Liu; Elebeoba E. May; Peter Ortoleva; Aleksander S. Popel; James P. Sluka; Jing Su; Paolo Vicini; Xiaobo Zhou; David M. Eckmann (Annals of Biomedical Engineering, 2016)

Estimation of impulse response between electromyogram signals for use in conduction delay distribution estimation - Tahsin Hassan; Kyle C. D. McIntosh; David A. Gabriel; Edward A. Clancy (Medical & Biological Engineering & Computing, 2013)

Reliability and variability of sleep and activity as biomarkers of ageing in Drosophila - Sofocles Koudounas; Edward W. Green; David Clancy (Biogerontology, 2012)

DmWRNexo is a 3′–5′ exonuclease: phenotypic and biochemical characterization of mutants of the Drosophila orthologue of human WRN exonuclease - Ivan Boubriak; Penelope A. Mason; David J. Clancy; Joel Dockray; Robert D. C. Saunders; Lynne S. Cox (Biogerontology, 2009)